A COMPARATIVE ANALYSIS OF RESEARCH AND DEVELOPMENT EXPENDITURES AND PATENT APPLICATIONS IN OECD COUNTRIES WITHIN THE CONTEXT OF GROSS DOMESTIC PRODUCT: THE CASE OF TÜRKİYE, MEXICO AND JAPAN - KOÇ, Refik Erdem (SSD Journal, 2025)
Growth and development are the elements that form the basis of countries’ economic policies. Technological developments and innovation investments are very important in the development and growth process. In endogenous growth theories that examine the foundations of technological developments, the importance of research and development (R&D) activities is emphasized.Research and development (R&D) is one of the most important variables that define any technological level. R&D expenditures are considered a key strategy that provides economic growth and innovation thanks to the technological potential they create. The aim of this study is to compare Turkey, Japan and Mexico, which are among the OECD countries, in terms of the relationship between R&D/Patent expenditures and development.For this purpose, comparative and descriptive analysis methods were applied on secondary data of selected indicators from the OECD and Turkish Statistical Institute (TUIK) databases for the period 2014-2023. A relationship was sought and interpreted between R&D expenditures, patent applications and GDP on the basis of the countries included in the study. As a result of the study, it was seen that Japan’s investment in R&D expenditures and its equivalent are much higher than Turkey and Mexico. It was seen that R&D investments in Turkey are higher than Mexico in terms of GDP. It can be said that Turkey’s R&D expenditures are low according to the OECD average, but Turkey attaches more importance to R&D expenditures than Mexico. It was concluded that Turkey’s R&D expenditures have increased even more in recent years and that structural reforms are necessary in terms of R&D investments in order to gain competitive advantage at the global level.